ANALISANDO A RELAÇÃO DAS VARIÁVEIS MACROECONÔMICAS COM O MERCADO ACIONÁRIO - Pasquini, Elaine Silvia (2008)
Macroeconomical variables that interfere in the economy and contagy that came of from worldwide crisis is the main theme which worries researchers of the financing area. Since 1980, that is the studied period of this research, the Stock Market brings huge amounts of profit in the shares of the companies of open capital, at the same time in that it scares the stock market holders, due to the volatile behaviour of its outcomes. The scope of this work is to identify if there is a relation between this behaviour of these macro economical variables and the obtained outcome by the national companies, which happens because of the behaviour of the macro economical crisis. Done the analysis of the Main Components, it is concluded that the macro economical variables have a fundamental importance in the action that determines the return index BOVESPA.(AU)